2018
DOI: 10.1186/s13256-017-1554-2
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary disease-free survival in a rare malignant extrarenal rhabdoid tumor: a case report and review of the literature

Abstract: BackgroundMalignant extrarenal rhabdoid tumor of the gastrointestinal tract is rarely reported in the literature. It is characterized by poor prognosis and aggressive metastatic features.A literature review evidenced only 19 cases, with poor outcome.Case presentationWe report a case of a colonic “pure” malignant extrarenal rhabdoid tumor with metastatic nodes in a 65-year-old Caucasian man. He was treated surgically with no recurrence, no adjuvant chemotherapy, and with 4-year survival without disease at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A careful review of the MEDLINE literature revealed 39 cases of CRbCs that should be added to our seven cases for a total of 46 cases [1,2,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] (Table S3). The patients were 22 males and 24 females aged 23–87 years (mean age: 64 years; median 69 years).…”
Section: Resultsmentioning
confidence: 99%
“…A careful review of the MEDLINE literature revealed 39 cases of CRbCs that should be added to our seven cases for a total of 46 cases [1,2,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] (Table S3). The patients were 22 males and 24 females aged 23–87 years (mean age: 64 years; median 69 years).…”
Section: Resultsmentioning
confidence: 99%
“…13 Adult cases are even more uncommon. 14 Accompanying such sparse incidence comes a dismal prognosis, with a majority of patients expiring within 6–8 months of diagnosis despite aggressive therapy and regardless of age. 2,11 These data are difficult to interpret, however, due to the paucity of documented adult cases and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Large intestine-derived malignant tumors with rhabdoid features are rare [ 12 ], and to date, only 28 cases (including the current case) of colorectal undifferentiated carcinoma with rhabdoid features have been reported (Table 1 ) [ 1 , 5 , 12 36 ]. These cases have been reported in 17 men and 11 women.…”
Section: Discussionmentioning
confidence: 99%